The space of media usage in Finland, 2007 and 2018 - Purhonen Semi; Leguina Adrian; Heikkilä Riie (Nordicom Review)
In Nordic countries and beyond, there exists a lack of longitudinal, population-level research focused on sociopolitical polarisation and the proliferation of new online activities in the context of changing media usage. In this article, we examine media usage in Finland in 2007 and 2018. We use two nationally representative surveys (N = 1,388 in 2007 and N = 1,425 in 2018) to make comparisons over time and include a wide set of media usage indicators. Applying multiple correspondence analysis, we assess the impact of the proliferation of online activities on the structure of the space of media usage and examine whether the association between media usage and sociopolitical divisions has become more sharply pronounced. The results suggest stability of the structure of media use rather than dramatic change. We discuss these results by reflecting on the relatively strong persistence of “traditional” models of stratification in digital cultural consumption and media practices.